The Importance and Value of Older Employees Wise Workers in the Workplace - Hilsen, Anne Inga; Olsen, Dorothy Sutherland (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2021)
'This book reports on original research and provides a positive consideration of the contribution of older workers. The existing literature tends to focus on the barriers, discrimination and problems, which older workers face so this is a useful corrective to that. The book will be of interest to both practitioners and researchers in the field.' -Sarah Vickerstaff, Professor of Work and Employment, Research and Innovation Application Mentor, School of Social Policy, Sociology and Social Research, University of Kent 'The proportion of older people at work is increasing for many reasons and we need to ensure that the resources they offer are well-used. This highly readable book makes clear how older workers add wisdom to competence. The lively interviews at the heart of the book reveal the generous relational work that is such wisdom. Older workers share their knowledge, create safe environments and build bridges, all in the interests of their organisation. They are also keen to learn. We too can learn from this book how we can value these wise workers.' -Anne Edwards, Professor of Education, University of Oxford 'I really hope this book will help to rethink both competence and skills development among older workers.' -Roger Moen, Head of R&D, Centre for Senior Policy, Norway 'Anne Inga Hilsen brought an infectious youthful enthusiasm to her research on older workers, which was founded on her extensive experience of Action Research. This highly readable book with Dorothy Olsen opens up discussion of this important field. With a starting point in the distinctive context of Norway, the authors explore differences in international policy contexts and theoretical perspectives. It should be essential reading for all who are concerned with knowledge, working life and HR.' -Richard Ennals, Emeritus Professor, Kingston University, UK. Adjunct Professor, University of Agder and NTNU, Norway Anne Inga Hilsen is a researcher at Fafo Institute of Labour and Social Research. She is also Associate Professor at the Department of Health and Social Work, University of South-Eastern Norway. Dorothy Sutherland Olsen is a senior researcher at the Nordic Institute for Studies in Innovation, Research and Education (NIFU).